1980
DOI: 10.1111/j.1365-2389.1980.tb02097.x
|View full text |Cite
|
Sign up to set email alerts
|

The Monosaccharide Composition of Polysaccharides in Ando Soils

Abstract: The monosaccharide composition of Ando soils, which originate from volcanic ash and have high organic matter content (8-21% carbon), was quite different from that of non-volcanic ash soils (1.2-1.9% carbon), being richer in mannose, fucose and ribose, whereas there was less glucose in cellulose-like form. arabinose, xylose and rhamnose. The Ando soils were also characterized by a lower percentage of organic carbon in the form of saccharide (4.4-7.4%) in comparison with non-volcanic ash soils (10.5%), though th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
25
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 21 publications
3
25
0
Order By: Relevance
“…For the release of monosaccharides, soil samples were hydrolyzed stepwise with 2.5 M H 2 S0 4 firstly as a primary hydrolysis, and with 0.5 M 11 2 50, after soaking with 13 M H 2 SO, as a secondary hydrolysis (20), essentially according to the procedure of 0ADES et al (25). The hydrolysate was neutralized with sodium hydroxide solution or Ba(OHh solution.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…For the release of monosaccharides, soil samples were hydrolyzed stepwise with 2.5 M H 2 S0 4 firstly as a primary hydrolysis, and with 0.5 M 11 2 50, after soaking with 13 M H 2 SO, as a secondary hydrolysis (20), essentially according to the procedure of 0ADES et al (25). The hydrolysate was neutralized with sodium hydroxide solution or Ba(OHh solution.…”
Section: Methodsmentioning
confidence: 99%
“…The ratio of the non-cellulosic to the cellulosic glucose (glucose(A)/glucose(D)) became larger on incubation. Considering the origin of the soil polysaccharides, the molar ratio of xylose to mannose was calculated by the author (19,20). The ratio for the upland field fell as the experiment progressed, but this tendency was not noticeable up to 18 months in the paddy field .…”
Section: Changes In Monosaccharide Composition Of the Bagged And Burimentioning
confidence: 99%
See 2 more Smart Citations
“…According to Murayama (1980), the amount of neutral sugars in volcanic ash soils which ranged from 4.4 to 7.4% of SOM was relatively small compared with 10.5% of SOM in non-volcanic ash soils. Moreover Murayama (1984b) and Folsom et al (1974) reported that the correlation between the amount of neutral sugars and total carbon (TC) was positively significant.…”
mentioning
confidence: 99%